2021
DOI: 10.7554/elife.69726
|View full text |Cite
|
Sign up to set email alerts
|

Rad53 checkpoint kinase regulation of DNA replication fork rate via Mrc1 phosphorylation

Abstract: The Rad53 DNA checkpoint protein kinase plays multiple roles in the budding yeast cell response to DNA replication stress. Key amongst these is its enigmatic role in safeguarding DNA replication forks. Using DNA replication reactions reconstituted with purified proteins, we show Rad53 phosphorylation of Sld3/7 or Dbf4-dependent kinase blocks replication initiation whilst phosphorylation of Mrc1 or Mcm10 slows elongation. Mrc1 phosphorylation is necessary and sufficient to slow replication forks in complete rea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 55 publications
3
36
0
Order By: Relevance
“…Hyper-phosphorylated Rad53 is undetectable in unperturbed mcm3-2KR cells (Fig 5D ), indicating that spontaneous DNA damage or replication stress is below the detection limit. Hydroxyurea (HU) treatment causes stalled DNA replication forks, which trigger Rad53 hyper-activation via the Mrc1 adaptor in the DNA replisome [37][38][39][40]. HU-induced (or Phleomycin-induced) Rad53 activation is dampened in mcm3-2KR cells compared to WT cells, consistent with the idea that Rad53 activation requires signaling via an intact DNA replisome, and that replisome levels are lowered in the mcm3-KR cells.…”
Section: Plos Geneticssupporting
confidence: 60%
“…Hyper-phosphorylated Rad53 is undetectable in unperturbed mcm3-2KR cells (Fig 5D ), indicating that spontaneous DNA damage or replication stress is below the detection limit. Hydroxyurea (HU) treatment causes stalled DNA replication forks, which trigger Rad53 hyper-activation via the Mrc1 adaptor in the DNA replisome [37][38][39][40]. HU-induced (or Phleomycin-induced) Rad53 activation is dampened in mcm3-2KR cells compared to WT cells, consistent with the idea that Rad53 activation requires signaling via an intact DNA replisome, and that replisome levels are lowered in the mcm3-KR cells.…”
Section: Plos Geneticssupporting
confidence: 60%
“…[59,99] Other in vitro studies using a reconstituted replication system have elaborated that Mrc1 stimulates the activity of both the CMG helicase and Pol ε. [100,101] Further experiments using this system have shown that Rad53 phosphorylates Mrc1 and thereby suppresses its ability to stimulate DNA synthesis. Together, we propose that Rad53 phosphorylates Mrc1, which in turn slows down leading strand DNA synthesis under replication stress.…”
Section: Mechanistic Insights Into How Rad53 Couples Leading and Lagg...mentioning
confidence: 99%
“…Other studies have shown that Rad53 phosphorylates Mrc1, which may in turn inhibit the ability of Mrc1-Tof1-Csm3 to stimulate CMG helicase activity and potentially the activity of Pol ε as well. [8,88,100] Therefore, we hypothesize that Rad53 phosphorylates multiple replisome components to slow down DNA synthesis of leading and lagging strands simultaneously (Figure 2). Because the machinery involved in leading and lagging strand DNA synthesis function autonomously in vitro, we further suggest that these actions couple leading and lagging strand DNA synthesis and thereby prevent deleterious ssDNA template exposure under replication stress.…”
Section: Mechanistic Insights Into How Rad53 Couples Leading and Lagg...mentioning
confidence: 99%
“…It has been shown that the budding yeast ortholog of the checkpoint adaptor protein Claspin, together with the Timeless:Tipin orthologs, is required to maintain coupling between the CMG helicase and the replisome [ 79 , 80 , 81 ]. Both budding yeast and human Claspin are required to regulate replication fork speed [ 82 , 83 , 84 ].…”
Section: Beyond Replication Initiation: the Role Of Ddk In Replicatio...mentioning
confidence: 99%